Menaquinone-4 modulates the expression levels of calcification-associated factors to inhibit calcification of rat aortic vascular smooth muscle cells in a dose-dependent manner - Cui, Liwen (Exp Ther Med, 2018)
Vascular calcification (VC) caused by chronic kidney disease (CKD)-mineral and bone disorder is a common complication of CKD. Recent studies have demonstrated that menaquinone-4 (MK-4) is negativly associated with VC in patients with CKD. Furthermore, we have previously shown that runt-related transcription factor 2 (Runx2) is important in the phenotypic transformation process of rat vascular smooth muscle cells (VSMCs), which is the key step for the development of VC. The present study investigated the influence of MK-4 on the phenotypic transformation process of rat VSMCs in order to illustrate its role in the process of VC. Calcification assays were perfomed to access the calcified degree of rat VSMCs. Additionally, the genes and proteins related to phenotypic transformation were measured by reverse transcription-polymerase chain reaction and western blotting methods. It was revealed that calcium deposition in the cells was evidently increased with an addition of β-glycerophosphate (β-GP) and could be completely prevented by co-incubation with MK-4 in a dose-dependent manner. Furthermore, the expression of Runx2 in the β-GP-induced VSMCs was inhibited by MK-4. It was also revealed that the expression of SMAD1 and bone morphogenetic protein (BMP)-2 were decreased in the β-GP-induced VSMCs treated with MK-4 in a dose-dependent manner; however, the expression of SMAD7 was increased in the β-GP-induced VSMCs treated with MK-4 in a dose-dependent manner. These observations suggest that MK-4 reduces mineralization by regulating the BMP-2 signaling pathway in order to attenuate the expression of Runx2.